Conservation and Restoration Measures in NIAZ ‘Olbia’, NAS Of Ukraine (to the 100th Anniversary of Taking Olbia Under Protection) - Alla Bujskikh; Sergii Shein (Емінак, 2021)
Olbia Pontica, being the prominent archaeological site and one of the biggest Northern Black Sea poleis, was taken under state protection in September, 1921. Since that the renovation work concentrated at the natural exhibition of the ancient buildings has become the priority of the research in National Reserve «Olbia», National Academy of Sciences of Ukraine. The paper presents the results of current conservation and restoration work carried out in Olbia to expose the open-air ancient architectural objects excavated more than a hundred years ago. The history of their protection, various methods of work, and series of activities carried out on the site of residential buildings in the Lower City, excavated in 1910-1911, the fortifications, excavated in 1904, the burial crypt excavated in 1901, are studied.At the area of the Hellenistic residential buildings in the Lower City the following rehabilitation works were done in 2004-2005, 2016-2018: the transversal street with steps and its supporting wall near the house NGF-1 were renewed, the well with original water-supply was cleaned, two wells at the corners of the inner court yards in houses NGF-1 and NGF-2 were cleaned and restored in their upper parts, the steps to the cellar in the house NGF-1 was restored completely. In 2020 a series of conservation works started at the area of the Roman defensive wall and three-chambers tower. With the help of the specially calculated building facilities, the heavy stone blocks that were fallen down the wall were taken back and fixed at their original positions. The next step would be the restoration of the inner walls in the tower, destroyed by the natural factor.The annual restoration and renovation work in Olbian Reserve is in the focus of its research activity that is closely connected with the preserving of the ancient city open-air exhibition for future generations.